Perceived participation and autonomy structural relationships among related factors in patients with stroke and hypertension in China: A ISM model approach - Wan, Le-ping; Yang, Guang-mei; Dong, Hai-ying; Liang, Xiao-xiao; He, Yan (Frontiers in Public Health, 2023)
Aims: To explore the structural relationship between perceived participation and autonomy among oleder adults with stroke and hypertension in home and community-based services (HCBSs) in the eastern coastal region of China. Design: An explorative cross-sectional study. Methods: From July to September 2021, a total of 714 respondents were reported to have stroke and hypertension, and their information was used in the analysis of this study. Multiple linear regression analysis was used to explore the factors influencing factors older adults' perceived participation and autonomy. Using the ISM model, we analyzed the factors affecting social participation in patients with stroke and hypertension and explained the logical relationships and hierarchy among the factors. Results: The mean score of perceived participation was 58.34±27.57. Age, marital status, health insurance, living status, number of children, chronic diseases, sleep time, frequency of outings, health utility value were significant factors affecting perceived participation and autonomy with stroke and hypertension patients. Among them, health insurance is the direct factors on the surface, age, number of children, chronic diseases, sleep time, frequency of outings, health utility value are the intermediate indirect factors, marital status, living status are the deep-rooted factors. Conclusion: By the study that the hierarchical structure provides a visualization of interrelationships and interdependences among the influencing factors of perceived participation and autonomy. It also may be a significant complement to traditional variable-entered approaches and construct an optimized multidimensional perspective of participation and autonomy. Future research should focus on optimizing the living environment of older adults with stroke and hypertension to explore the model of rehabilitative intervention and help patients successfully reintegrate into their families/societies.